Model-Model Kesejahteraan Mental Dari Perspektif Islam: Satu Sorotan Literatur: Models of Mental Well-Being from an Islamic Perspective: A Literature Review - Sulaiman , Rohaya; Hj. Basri , Fairuzah; Mahfuzah Mohammed Zabidi , (Online Journal of Research in Islamic Studies, 2021)
Mental well-being plays an important role in determining the direction of life. It is closely related to physical well -being, community well-being and the achievement of life goals. Of late, mental well-being has become a global issue that is also seen in Malaysia. Reports of an increase in cases related to violations of social welfare on a daily basis show that the problem is getting more serious. More worryingly, this problem is also faced by Muslims who adhere to Islam. This situation seems to indicate the existence of a question about the level of Islamic understanding of Islamic law. Thus, this article aims to examine aspects of mental well-being according to the views of Islamic scholars. This study uses the library research method with a document analysis approach to the writings of Islamic scholars. The results of this study found that Islamic scholars since the heyday of Islamic scholars have discussed aspects of mental well-being using the method of spiritual well-being. In this regard, there are five models of mental well-being that have been highlighted by Islamic scholars. First, the model of Tazkiyah al-Nafs which is the model of psychotherapy according to Imam al-Ghazali. Second, the model of Tahaqquq Tazkiyah al-Nafs according to Sa’id by Hawwa. Third, the model of the approach of Sufism and morality in the purification of the soul. Fourth, Abu Talib al-Makki's model of Human Psychological Development based on the Book of Qut al-Qulub. Fifth, the model of Spiritual Healing in the Sufi Tradition. These five models of mental well-being use the approach of purification of the soul with emphasis on moral aspects and Sufism after understanding the aqidah and the practice of worship based on Islamic law. This model is particularly useful to psychiatrists, psychologists, counsellors and individuals with mental problems as well as the families involved.